Pengembangan Kreativitas melalui Pemanfaatan Barang Bekas Menjadi Produk Kerajinan di Panti Asuhan Yarhima Bondowoso, Jawa Timur - Zaskia Ulfa Ningrum; Isma’ani Hasanatur Rohmah; Widiasih Kusmawati; Khofifatul Hikmah; Fahry Al Fatah; Muhammad Hibatullah; Agung Nugroho Puspito (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Creativity is the ability to come up with new, useful, and different ideas or works from what already exists (Munandar, 2009). This community service activity aims to foster creativity and environmental awareness among the children at Yarhima Bondowoso Orphanage through training on how to use recycled materials. The methods used included giving presentations, discussions, demonstrations, hands-on practice, and guidance, involving 15 participants. Evaluation was done using a one-group pre-test and post-test design, along with observations. The evaluation tool consisted of 15 multiple-choice questions about creativity and recycling. The results showed that the participants' average scores increased from 10.20 to 12.87, a 26% improvement. Participants also successfully made crafts from used materials such as piggy banks, flower pots, and simple trash bins. Besides improving skills and creativity, this activity also raised the participants' awareness about reusing items that are no longer in use. Thus, this training is effective for developing creativity and an environmentally caring character in orphanage children.